(untitled) (Journal of Atomic and Molecular Sciences, 2017)
To rely mainly on the impact of external electric field derived from the electronic coupling charge transfer rate in the change, the new theoretical method can not merely a better understanding of chemical structure, the external electric field and optoelectronic properties of donor(D)-acceptor(A) system, but also can be used for reasonable design of D-A system of novel organic solar cells. This article selects PC70BM (phenyl-fullerenes-butyric acid methyl ester) (good solubility, high electron mobility, with common polymer material to take shape a fine phase separation) as this acceptor; low five different kinds of chain length of oligonaphthofurans molecules (active material of fluorescent probe molecule) as the donor, using density functional theory on the basis of the Marcus theory to calculate the electronic coupling, reorganization energy, gibbs free energy of reaction, rates of the charge recombination and the rates of exciton dissociation for this study.